Students’ attitude in learning English as a foreign language. - Herrera Tapia, Lorena Gabriela (2023)
Students' attitude in learning English as a foreign language emphasizes the importance of acquiring the language for different purposes, not only to approve the subject. Some researchers demonstrate that the student's attitudes can be positive or negative, and different factors determine them. The purpose of this research was to identify the possible factors that intervene in students' attitudes toward learning English as a foreign language in the first, second, and third levels of English Major at the Technical University of Cotopaxi, Pujilí campus, April - August 2022 academic period. The population of this research was 148 students The methodology used in this study was descriptive with a quantitative approach. A survey was applied, and for the data analysis, the Statistical Package for Social Sciences (SPSS) program was used. The study showed that students do not have attitudinal problems toward learning English. They really like the English language, and they have different purposes to acquire the language such as to get a good job, travel around the world, get a good job position, know a new culture, among others. In this sense, the identified factors in this research intervene positively in the English language learning of the students. However, it is recommended to carry out another study to find out what factors influence students to drop out of this career or lose the subject.